"The Further We Stretch the Higher the Sky" - On the Impact of Wage Increases on Job Satisfaction - Christian Grund; Dirk Sliwka (University of Bonn, Bonn Graduate School of Economics (BGSE), 2003)
The impact of wage increases on job satisfaction is explored. First, it is empirically confirmed that current job satisfaction rises with the absolute wage level as well as with wage increases. Second, a basic job satisfaction function is constructed based on the empirical results, and theoretical implications are analyzed. Myopic maximization of such a function directly implies increasing and concave shaped wage profiles. It is shown that employees get unhappier over time staying on a certain job although wages increase, which again is empirically confirmed.
Keywords: M12; J28; M54; J30; 330; Job satisfaction; Wage increases; Habit formation; Wage profiles; Relative utility; Lohn; Arbeitszufriedenheit; Schätzung; Deutschland